Masyarakat Adat dan Hak Konstitusional Atas Tanah di Era Ibu Kota Baru (IKN) (International Forum of Researchers and Lecturers, 2025)
The establishment of Indonesia's new capital city (IKN) in East Kalimantan is a major achievement in the nation's strategic plan. This enormous project poses significant legal issues concerning the constitutional land rights of Indigenous peoples who have been in the region for millennia. This study seeks to analyze the recognition and probable jeopardization of Indigenous communities' constitutional rights within the legal framework of the IKN project. The study employs a normative legal framework and examines regulations, including Law No. 3 of 2022 concerning the Capital City and pertinent Constitutional Court rulings on Indigenous rights, highlighting a disparity between formal legal acknowledgment and actual enforcement. Preliminary findings suggest minimal Indigenous involvement in planning and decision-making processes, coupled with escalating dangers of land confiscation. The study advocates for enhanced constitutional protections and the realization of land rights as a means of restorative justice and acknowledgment of Indigenous identity within the framework of national development.